Pengaruh Diversitas dan Inklusi Terhadap Kinerja Organisasi - Vera Herlina Mustari; Sari Zulfiana Hasan; Moh. Muklis Sulaeman; Fatimah Malini Lubis; Agus Suyatno (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The influence of diversity and inclusion in the context of organizations has become a major focus in the modern business world. The growing complexity of the global business environment and the demands of diverse markets require organizations to better understand, value, and leverage employee diversity. The aim is to analyze the Analysis of the Effect of Diversity and Inclusion on Organizational Performance. The research method used is a literature study or Library Research with a qualitative approach. Based on the problems, objectives, research results and discussion, the following conclusions can be drawn. The management of deversity and inclusion has the view that the differences that exist in individuals are very valuable resources and need to be put to good use. Keywords: Diversity, Inclusion, Orhanization Performance